Preparation of microvillus-like nitrogen-doped carbon nanotubes as the cathode of a microbial fuel cell. Issue 5 (8th December 2015) - He, Yan-Rong; Du, Feng; Huang, Yu-Xi; Dai, Li-Ming; Li, Wen-Wei; Yu, Han-Qing
Abstract : The efficiency of a microbial fuel cell (MFC) generally suffers from its poor cathode performance. To improve this, a novel cathode material was prepared by growing vertically aligned nitrogen-doped carbon nanotubes on carbon cloth, offering an efficient, metal-free, and low-cost alternative to Pt/C. Abstract : A microbial fuel cell (MFC) is an emerging technology to harvest electricity from waste, but generally suffers from low power density at the present stage. Especially, the poor cathode performance usually presents a limiting factor. In this work, we prepare a novel cathode material for an MFC by growing vertically-aligned nitrogen-doped carbon nanotubes (N-CNTs) on carbon cloth (CC) using a chemical vapor deposition method, and evaluate its performance in MFC tests. The results show that the MFC with the N-CNT–CC as its cathode exhibits an output power density of 542 mW m −3, greater than that of the MFC with the Pt/C-coated CC cathode. The electrochemical experimental results show higher catalytic activity for oxygen reduction and a smaller resistance of the N-CNT–CC electrode, compared to those of the Pt/C-CC, which are responsible for its better MFC performance. The N-CNT–CC material prepared in this work may offer an appealing metal-free and low-cost alternative to Pt/C for MFC cathode applications.